Drug allergy passport and other documentation for patients with drug hypersensitivity – An ENDA/EAACI Drug Allergy Interest Group Position Paper. Issue 11 (14th August 2016) - Brockow, K.; Aberer, W.; Atanaskovic‐Markovic, M.; Bavbek, S.; Bircher, A.; Bilo, B.; Blanca, M.; Bonadonna, P.; Burbach, G.; Calogiuri, G.; Caruso, C.; Celik, G.; et al.
Abstract: The strongest and best‐documented risk factor for drug hypersensitivity (DH) is the history of a previous reaction. Accidental exposures to drugs may lead to severe or even fatal reactions in sensitized patients. Preventable prescription errors are common. They are often due to inadequate medical history or poor risk assessment of recurrence of drug reaction. Proper documentation is essential information for the doctor to make sound therapeutic decision. The European Network on Drug Allergy and Drug Allergy Interest Group of the European Academy of Allergy and Clinical Immunology have formed a task force and developed a drug allergy passport as well as general guidelines of drug allergy documentation. A drug allergy passport, a drug allergy alert card, a certificate, and a discharge letter after medical evaluation are adequate means to document DH in a patient. They are to be handed to the patient who is advised to carry the documentation at all times especially when away from home. A drug allergy passport should at least contain information on the culprit drug(s) including international nonproprietary name, clinical manifestations including severity, diagnostic measures, potential cross‐reactivity, alternative drugs to prescribe, and where more detailed information can be obtained from the issuer. It should be given to patients only after full allergy workup. In the future, electronic prescription systems with alert functions will become more common and should include the same information as in paper‐based documentation.